"Amyloid‐beta accumulation cycle" as a prevention and/or therapy target for Alzheimer's disease. Issue 3 (25th January 2020) - Rao, Chinthalapally V.; Asch, Adam S.; Carr, Daniel J. J.; Yamada, Hiroshi Y.
Abstract: The cell cycle and its regulators are validated targets for cancer drugs. Reagents that target cells in a specific cell cycle phase (e.g., antimitotics or DNA synthesis inhibitors/replication stress inducers) have demonstrated success as broad‐spectrum anticancer drugs. Cyclin‐dependent kinases (CDKs) are drivers of cell cycle transitions. A CDK inhibitor, flavopiridol/alvocidib, is an FDA‐approved drug for acute myeloid leukemia. Alzheimer's disease (AD) is another serious issue in contemporary medicine. The cause of AD remains elusive, although a critical role of latent amyloid‐beta accumulation has emerged. Existing AD drug research and development targets include amyloid, amyloid metabolism/catabolism, tau, inflammation, cholesterol, the cholinergic system, and other neurotransmitters. However, none have been validated as therapeutically effective targets. Recent reports from AD‐omics and preclinical animal models provided data supporting the long‐standing notion that cell cycle progression and/or mitosis may be a valid target for AD prevention and/or therapy. This review will summarize the recent developments in AD research: (a) Mitotic re‐entry, leading to the "amyloid‐beta accumulation cycle, " may be a prerequisite for amyloid‐beta accumulation and AD pathology development; (b) AD‐associated pathogens can cause cell cycle errors; (c) thirteen among 37 human AD genetic risk genes may be functionally involved in the cell cycle and/or mitosis; and (d) preclinical AD mouse models treated with CDK inhibitor showed improvements in cognitive/behavioral symptoms. If the "amyloid‐beta accumulation cycle is an AD drug target" concept is proven, repurposing of cancer drugs may emerge as a new, fast‐track approach for AD management in the clinic setting. Abstract : "Amyloid‐beta accumulation cycle". Amyloid‐beta accumulation occurs in early latent phase of Alzheimer's disease, triggering its pathology development, yet the mechanism has been elusive. This integrated hypothesis explains that amyloid‐beta accumulation occurs as a vicious cycle and offers insights on how the cycle may be interfered by cell cycle‐ or mitosis‐targeting drugs.